Emigrate “to make life better” in Vale do Ave (1960s-1970s): economy, value and time - Rei, Mariana (2022)
This paper aims to understand the meaning of the expression “making life better” in an industrialized region of Vale do Ave, considering the changes during the 1960s-1970s in Portugal and in the long term. It addresses, particularly, the expectations of improvement in living conditions that this expression condenses, conveying ideas about the future, against a past in which life “didn’t run forward”, and a life in which one has “always worked” to “keep earning a living”. It is argued that the “work” implied in this expression reflects a tension between the need to “making a living” and the aspirations towards a “good life”, articulating economy, value and time.